Advancing Emergency Medicine Training: The Crucial Role of Ultrasound Simulators in Efast Education - Turbanova Umida Valiyevna (Global Scientific Publishing, 2023)
In the rapidly evolving landscape of emergency medicine, the Extended Focused Assessment with Sonography in Trauma (eFAST) has become indispensable for swift and accurate trauma patient assessments. This article delves into the transformative role of ultrasound simulators in addressing the challenges associated with traditional eFAST training methods. The significance of eFAST lies in its ability to expedite diagnoses of life-threatening conditions, demanding a skill set that traditional approaches often struggle to cultivate
Keywords: significance; threatening; swift; landscape